Effect of Tamsulosin on Stone Clearance after Extra-corporeal Shock Wave Lithotripsy - Hossain, MZ; Biswas, NP; Islam, MS; Hossain, MZ; Shameem, IA; Kibria, S (Bangladesh Medical Journal, 2012)
This prospective study was performed to observe effect of Tamsulosin on stone clearance after Extra-corporeal Shock Wave Lithotripsy (ESWL) for renal stones having size 6-20 mm. According to selection criterion total 80 patients with renal stones were divided into two groups. In group l, 40 patients treated with traditional hydrotherapy after ESWL and in group 2 another 40 patients were treated with additional Tamsulosin. In-group 1, there were 25 male and 15 female patients and in group 2, male and female patients were 30 and 10 respectively. Without considering the stone size within 3 weeks after ESWL stone clearance in group 1 and 2 was 57.50 and 80.00 percent respectively (P<0.05). Considering the stone size, stone clearance in group 1 was 50% and 33.3% among smaller (6-10 mm) and larger (11-20 mm) stones and in group 2 was 50% and 66.7% among smaller and larger stone respectively (P>0.05). In cases of smaller stones, clearance was 100% and 77.8% among group 1 and 2 respectively without any significant difference (P>0.05). But in larger stones, stone clearance was 34.60% and 81.8% among group 1 and 2 respectively and there was a statistically significant difference in clearance between the groups (P<0.05). Morbidity was significantly lower when ESWL was combined with Tamsulosin. Requirement of additional interventional procedures were significantly higher in group 1 (P<0.05). Complications were less common in group 2 than group 1. Haematuria and lower urinary tract symptoms were equally common in both groups. DOI: http://dx.doi.org/10.3329/bmj.v40i1.9959 BMJ 2011; 40(1): 27-32